2023
DOI: 10.1002/cncr.35004
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant cyclophosphamide versus antithymocyte globulin in patients with acute lymphoblastic leukemia treated with allogeneic hematopoietic cell transplantation from matched unrelated donors: A study from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation

Sebastian Giebel,
Myriam Labopin,
Urpu Salmenniemi
et al.

Abstract: BackgroundThe aim of this study was to compare two immunosuppressive strategies, based on the use of either rabbit antithymocyte globulin (ATG) or posttransplant cyclophosphamide (PTCY), as a prophylaxis of graft‐versus‐host disease (GVHD) for patients with acute lymphoblastic leukemia (ALL) in first complete remission who underwent hematopoietic cells transplantation from matched unrelated donors.MethodsOverall, 117 and 779 adult patients who received PTCY and ATG, respectively, between the years 2015 and 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
1
4
2
Order By: Relevance
“…Moreover, GvHD occurrence after PTCY was not different than that reported in the ATG group, regardless of underlying hematological malignancies-not only ALL-and type of HSCT donor, as the majority of our patients received HSCT from a haploidentical donor. However, Giebel et al have described a reduced risk of extensive chronic GvHD in ATG recipients by a multivariate analysis (hazard ratio, 0.54; 95%CI, 0.3-0.98; p = 0.04) [1], not observed in our cohort. Although GvHD incidence was comparable between groups, we observed a significant protection from hematological relapse in the PTCY arm, likely because of a prompter T cell compartment and anti-tumor immune surveillance reconstitution [23].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Moreover, GvHD occurrence after PTCY was not different than that reported in the ATG group, regardless of underlying hematological malignancies-not only ALL-and type of HSCT donor, as the majority of our patients received HSCT from a haploidentical donor. However, Giebel et al have described a reduced risk of extensive chronic GvHD in ATG recipients by a multivariate analysis (hazard ratio, 0.54; 95%CI, 0.3-0.98; p = 0.04) [1], not observed in our cohort. Although GvHD incidence was comparable between groups, we observed a significant protection from hematological relapse in the PTCY arm, likely because of a prompter T cell compartment and anti-tumor immune surveillance reconstitution [23].…”
Section: Discussioncontrasting
confidence: 81%
“…Giebel et al have reported a lower cumulative incidence of relapse at 2 years (18% vs. 25%; p = 0.046), of leukemia-free survival rates (71% vs. 59%; p = 0.01), and of OS in the PTCY group (82% vs. 74%; p = 0.08) compared to ATG [ 1 ]. In our real-life study including different types of hematological malignancies, a significant protection from relapse was confirmed in PTCY-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the PTCy cohort the authors observed improved LFS and OS [26]. Another study recently published by EBMT observed a reduced risk for extensive chronic GvHD and an inferior LFS as compared to the PTCy group in ALL patients receiving ATG and undergoing hematopoietic cell transplantation from a MUD [25]. For the whole cohort our results are in line with those of EBMT with no differences in overall survival or in the incidence of acute GvHD, but with a significantly higher incidence of chronic GvHD in the PTCy group as compared to ATG.…”
Section: Discussionmentioning
confidence: 86%
“…Aydin et al compared ATG versus PTCy in matched unrelated donors in a non-myeloablative conditioning setting with similar outcomes in both groups [24]. A comparison of PTCy versus ATLG in a considerable ALL cohort in terms of outcome is scarcely to be found in the literature [25,26]. Therefore, we aimed to compare PTCy and ATLG as GvHD prophylaxis in ALL patients who received a TBI containing conditioning regimen in terms of leukemia-free and overall survival, transplant-related mortality, relapse incidence and incidence of acute and chronic GvHD.…”
Section: Introductionmentioning
confidence: 99%